(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper analyzed the effect of magnetic fieldon 3-D flow of an incompressible viscous fluid passes through a porous platewith the following assumption; The upper plate is subjected to a constantsuction while the lower plate to a transverse sinusoidal injection velocitydistribution. The plate temperature is constant. A magnetic field is applied inthe direction normal to the plate. Three dimensional MHD flow. The governingnonlinear partial differential equations are the solved numerically using thefinite difference method and the expression for the velocity and thetemperature field are obtained. The effect of Hartman number M and suctionparameter R are observed on the velocity and temperature distribution.